Timing Six Energetic Rotation-Powered X-Ray Pulsars, Including the Fast-Spinning Young Psr J0058-7218 and Big Glitcher Psr J0537-6910 - Espinoza-Romo, C (Institute of Physics, 2022)
Measuring a pulsar’s rotational evolution is crucial to understanding the nature of the pulsar. Here, we provide updated timing models for the rotational evolution of six pulsars, five of which are rotation phase-connected using primarily NICER X-ray data. For the newly discovered fast energetic young pulsar, PSR J0058−7218, we increase the baseline of its timing model from 1.4 days to 8 months and not only measure more precisely its spin-down rate ν ̇ = ( − 6.2324 ± 0.0001 ) × 10 − 11 Hz s − 1 but also for the first time the second time derivative of its spin rate ν ̈ = ( 4.2 ± 0.2 ) × 10 − 21 Hz s − 2 . For the fastest and most energetic young pulsar, PSR J0537−6910 (with a 16 ms spin period), we detect four more glitches, for a total of 15 glitches over 4.5 yr of NICER monitoring, and show that its spin-down behavior continues to set this pulsar apart from all others, including a long-term braking index n = −1.234 ± 0.009 and interglitch braking indices that asymptote to ≲7 for long times after a glitch. For PSR J1101−6101, we measure a much more accurate spin-down rate that agrees with a previous value measured without phase connection. For PSR J1412+7922 (also known as Calvera), we extend the baseline of its timing model from our previous 1 yr model to 4.4 yr, and for PSR J1849−0001, we extend the baseline from 1.5 to 4.7 yr. We also present a long-term timing model of the energetic pulsar PSR J1813−1749, by fitting previous radio and X-ray spin frequencies from 2009-2019 and new ones measured here using 2018 NuSTAR and 2021 Chandra data. © 2022. The Author(s). Published by the American Astronomical Society.